The Professionalism Apparatus In Implementing The Technical Laboratory Unit Routine Maintenance Construction and Public Works Department East Kutai Regency - Atine Rustinawati Marsuq (ADMINISTRASI PUBLIK, 2017)
The aim of this study is to (1) determine Professionalism In UPT Laboratory Apparatus Construction and Routine Maintenance Unit Public Works Department of East Kutai. (2) to determine the factors that influence the professionalism of the UPT Laboratory Apparatus construction and routine maintenance unit of the Public Works Department of East Kutai. The method used is approach qualitative by Type phenomenological study collecting data obtained through observation, interviews, and documentation. The process of data analysis include data reduction, data presentation, and conclusion. The results showed that: (1) Professionalism of employees from the aspect of creativity shows the use of technology or social media to facilitate and expedite the work in addition to the use of narrow rooms including employee creativity. innovation is raised, namely the addition of a suggestion box and do additional financial administrator in each field, and then found the enthusiasm of employees in responding to innovation or new ideas in the bureaucracy (2) Factors that affect the professionalism that performance has indicators contained in the job analysis in the form of work results expected, accountability apparatus based on the size of the work that has been done in the form of documents, events, reports, draft, file and mail then the work is controlled by the leadership. Later inloyalty factor tends to lead to employee status TK2D temporary employees for civil servants loyalty tested in political engagement and on the capability of the apparatus can be seen from the distance training, experience and knowledge and managerial ability or technical ability.